Social Support for Post-Divorce Role Readjustment - Fachrina, Fachrina; Maihasni, Maihasni (Universitas Negeri Semarang, 2025)
Divorce causes changes in social roles and relationships both in the family and in the society. Readjustment requires greater attention and effort, especially by women, regarding the socio-economic impacts it causes. This research aims at explaing the forms of family social supports and social networks for post-divorce role readjustment. A qualitative approach was used by conducting in-depth interviews with eight deliberately selected participants who had experienced the divorce in the last one to three years and they had children. Social support from family and social networks have a significant positive impact on the post- divorce readjustment process. Key findings highlight that emotional, practical, and informational support and positive feedback play an important role in helping the individuals navigate their complex life changes after the divorce. Parents are the first parties to provide emotional support in the form of empathy, motivation, advice, and a place to share feelings as a form of self-acceptance for the children. Parents are also the source of material support to help finance living needs and child care. Support from social networks includes providing information about available resources or services and advice to overcome the post-divorce difficulties, but there is a relative lack of perceived support and positive responses. This research provides important insights with how social support can facilitate the post-divorce readjustment process and emphasizes the need to integrate the strategies for strengthening the social support into individual readjustment interventions.